The NATO generic destroyer – a shared geometry for collaborative research into modelling and simulation of shipboard helicopter launch and recovery. (15th May 2021) - Owen, Ieuan; Lee, Richard; Wall, Alanna; Fernandez, Nicholas
Abstract: The helicopter-ship dynamic interface is the environment above the landing deck of a ship where a helicopter pilot has to control the aircraft while contending with a moving deck and an unsteady airflow known as the ship airwake. Research into understanding this environment has included modelling the airwake using wind tunnel studies and Computational Fluid Dynamics, and has often used the Simple Frigate Shape (SFS), a generic ship geometry representative of a naval frigate. This paper reviews the contribution that the SFS has made to research into the helicopter-ship dynamic interface, and introduces a new ship geometry for future research. The new ship, developed within a NATO Research Task Group, is the NATO Generic Destroyer (NATO-GD), a concept ship with a simplified geometry that is more representative of a modern helicopter-enabled combat ship with a stealthy superstructure. As well as introducing the NATO-GD as a common platform for research, the paper also introduces a number of ship motion profiles to encourage new research that will include the effect of ship motion on the airwake. It is anticipated that future research on a common ship, with prescribed motion and adopting a common helicopter will lead to improved or new modelling methodologies. Highlights: A review of Simple Frigate Shape contribution to ship/helicopter dynamic interface research. The NATO Generic Destroyer is specified as a new generic ship for future research. Ship motion profiles are specified for future airwake research. Ship motion shown to inject additional energy into the airwake at the motion frequency.